The Law of Reversion And Attraction in Islam: Hukum Tarik-Menarik Dalam Islam - Fayyadh, Qays Farhan (Indonesian Journal of Islamic Studies, 2024)
General Background: The "law of attraction" has been widely discussed in psychology and spirituality, often centered on ideas of energy, intent, and outcome, primarily from a Western perspective. Specific Background: However, Islamic texts also address these concepts, framing them as divine laws that influence an individual’s actions and outcomes. Knowledge Gap: Despite these intersections, few studies have examined the laws of attraction and repulsion from both Islamic and psychological perspectives, highlighting a gap in understanding their practical implications within an Islamic framework. Aims: This research aims to provide a nuanced analysis of these laws, using linguistic and jurisprudential approaches to align Islamic beliefs with modern psychological concepts. Results: The findings indicate that Islamic teachings on attraction and repulsion foster moral and spiritual accountability, reinforcing that actions align with rewards or consequences through a divinely ordained system. Novelty: By integrating perspectives from Islamic texts with contemporary psychological theories, this study bridges a significant interpretative gap, showing how these laws can inform behavior within Islamic societies. Implications: This research explores the impact of Islamic and psychological concepts on attraction and repulsion, highlighting their potential to influence ethical behavior, social harmony, and personal growth across various cultural contexts. Highlights: Islam-Psychology Link: Integrates attraction and repulsion concepts across disciplines. Moral Consequences: Islamic view aligns actions with ethical and spiritual outcomes. Cultural Impact: Examines influence on behavior within Islamic societies. Keywords: Attraction, Repulsion, Islamic Law, Human Behavior, Psychological Influence